Léo Malet ou le roman noir américain made in France - Crystel Pinçonnat (Transatlantica)
An important critical tradition tends to consider Léo Malet as the father of the French noir novel. Though he owes his fame to the character of Nestor Burma that he invented in 1943, his previous production, which served as a testing ground to develop his Parisian version of noir fiction, is not as well-known. During the German Occupation of France, the publisher Georges Ventillard, taking advantage of the craze for noir fiction and the banning of Anglo-American literature in France, launched the “Minuit” series. The twenty-four French-produced titles that he published from 1941 to 1949 offered American plots, settings and characters. To reinforce their credibility, their authors adopted American-sounding pseudonyms. This is how Léo Malet, commissioned by “Minuit,” wrote the first Johnny Metal novel in 1941. With the Metal series, Malet imitated a form belonging to American tradition. Like most French novelists who produced these fake American novels, he did not know the United States. His main source of inspiration was not so much noir fiction as the movies. It is on this “American” production by Léo Malet that we will focus here. We will look at three of his best-known novels (Johnny Metal, Le Dé de jade and La Mort de Jim Licking), to show how Malet reappropriated the hard-boiled tradition through the lens of American cinema and reinvented it for the French public. A former member of the surrealist movement, Malet, in fact, did not copy but subverted the traditional aesthetics of noir fiction by injecting into it, among other things, the surrealist practice of décollage, a technique that breaks the barriers between literature and the visual arts.